Screening and determination of sulphonamide residues in bovine milk samples using a flow injection system - Bedatty Fernandes, Flavio Cesar [UNESP]; Silva, Aline Santana [UNESP]; Rufino, Jose Luiz [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Elsevier B.V., 2015)
A new, simple, rapid and sensitive flow injection spectrophotometric method was developed for the screening and determination of sulphonamides in bovine milk samples. The method is based on the condensation of sulphathiazole, sulphamethazine, and sulphadimethoxine with p-dimethylaminobenzaldehyde (p-DAB) in acid medium, in the presence of sodium dodecyl sulphate (SDS), producing a yellow compound (lambda(max) = 465 nm). Optimisation of the experimental parameters was performed using a multivariate methodology. The linear range was 90-500 mu g/L and the limits of detection and quantification were in the ranges 25-29 mu g/L and 84-88 mu g/L, respectively. The procedure was applied for the determination of sulphonamide antibiotics in bovine milk samples submitted to a prior extraction procedure based on QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) methodology. Recoveries of 60.5-70.5% were achieved for milk samples spiked with 0.09, 0.1, 0.2, and 0.3 mu g/g of each sulphonamide. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sulphonamides; p-Dimethylaminobenzaldehyde; Spectrophotometry; Screening; Flow injection analysis; Milk